The Implications of The Existence of The Alleged Criminal Acts of Corruption Towards the Implementation of The Construction Contract - Bondan Bayu Tetuko (Fakultas Hukum Universitas Hang Tuah, 2018)
Construction contracts are civil relations, and is an agreement, principle principle in Book III Civil Code, and in construction contracts are generally used for the achievement of common goals. Fulfilling the needs of goods and services is an important part of governance, In connection with this the emergence of negative implications on the problem of the neglect of construction services in the process constrained indications of corruption. Contract cancellation stage in legal doctrine in Indonesia is only limited to contract and pre contract phase but also possible in the implementation phase by considering the principle of presumption of innocence as well as the principle of legal certainty, the implementation of construction contracts should proceed accordingly without having to override the legal process that runs from parties that are indicated to be corrupt. In the event that the construction contract is carried out in accordance with the basic principles of government procurement of goods / services that are efficient, effective, open and competitive, transparent, fair and accountable, in order to achieve development goals equally and in accordance with the mandate of the constitution of the Republic of Indonesia.